Gaya Bahasa Pada Novel Bibi Gill Karya Tere Liye - Ari Nugraha; Nurwakhid Muliyono (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2022)
This study aims to describe the style of language in the novel Bibi GILL by Tere Liye and. The method used in this research is descriptive qualitative which is described and described in detail. Collecting data in this study using the method of documentation with the development of critical analysis. The data source is the novel Bibi Gill by Tere Liye, with data in the form of words, phrases or sentences that reflect the style of language. The results of this study indicate that Tere Liye's BIBI GILL novel contains various types of language styles, including comparative, contradictory, linking and repetition styles. The results of the research conducted can be used as teaching materials for literary learning.